2011
DOI: 10.3390/ijerph8030713
|View full text |Cite
|
Sign up to set email alerts
|

Three Potential Sources of Microfungi in a Treated Municipal Water Supply System in Sub-Tropical Australia

Abstract: Some microfungi are known to be opportunistic human pathogens, and there is a body of scientific opinion that one of their routes of infection may be water aerosols. Others have been implicated as causative agents of odours and off-tastes in drinking water. This study was undertaken to investigate three potential sources of microfungi in a treated, oligotrophic municipal water supply system in sub-tropical Australia. Formation of the microfungal component of developing biofilm on hard surfaces in water storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…detected filamentous fungi on replaced pipes from the same water network as described in the present results, confirming that filamentous fungi are able to grow as biofilms on pipe surfaces. These findings corroborate Doggett (2000) and Sammon et al (2011) who also detected filamentous fungal biofilms in replaced pipes. Nagy and Olson (1985) emphasize that older pipes support a more diverse community composed of diverse microorganisms, including filamentous fungi.…”
Section: In Situ Detectionsupporting
confidence: 89%
See 1 more Smart Citation
“…detected filamentous fungi on replaced pipes from the same water network as described in the present results, confirming that filamentous fungi are able to grow as biofilms on pipe surfaces. These findings corroborate Doggett (2000) and Sammon et al (2011) who also detected filamentous fungal biofilms in replaced pipes. Nagy and Olson (1985) emphasize that older pipes support a more diverse community composed of diverse microorganisms, including filamentous fungi.…”
Section: In Situ Detectionsupporting
confidence: 89%
“…Taylor et al (2001) identified 307 fungal species as emerging pathogens, and biofilms have been reported to contain some of these (WHO 2003). Nevertheless, reports of filamentous fungi in biofilms remain few and somewhat inconclusive (Doggett 2000;Kelley et al 2003;Sammon et al 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the A. fumigatus species has been found in hospital water samples (Araujo et al 2010;Hayette et al 2010). Consequently, as water-related activities could be a route of fungal transmission to the immunocompromised host (Anaissie et al 2002;Sammon et al 2011), the presence of V. vermiformis and A. fumigatus in hospital water could lead to an increase of nosocomial infections by this fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Since patulin-producing Penicillium species also have been isolated from the marine environment (Vansteelandt et al 2012), it is not clear whether the water from apple packing houses is directly responsible for the contamination of drinking water. Airborne spores may play an important role in contamination of water reservoirs (Sammon et al 2011). Many different species of Penicillium are known to produce patulin.…”
Section: Introductionmentioning
confidence: 99%